Enhancing Access to Energy Services for Sustainable Development in Rural Communities - Gyawali, Surya; Bajracharya, Sushil Bahadur; Tiwari, Sudarshan Raj; Skotte, Hans Norve (Journal of the Institute of Engineering, 2020)
Access to energy has been based on physical availability, acceptability, adequacy, affordability, reliability, and quality of supply. In addition to physical access, real access to energy services can be limited by the purchasing power of the household, the cost of energy and cost or energy-using equipment. However, ensuring adequate energy for a healthy life implies that the types and amount of energy should meet basic minimum needs without adverse health impacts. The purpose of the paper is to explore the dimensions of energy access to rural communities in developing countries for enhancing sustainable development objectives. The systematic literature review methodology has been used to define approaches of sustainability of energy access and try to understand the linkage between modern energy access to sustainable development for rural communities. The study is stabilized that, redefinition and standard thresholds for sustainable energy services in local community level are crucial for human welfare and health, efficiency and productivity, as well as impacts on the environment, must be linked with sustainable development. Measuring sufficiency or adequacy is harder to define because this may vary from amazingly from region to region depending on climate, customs, and living standards. The study provides a unique insight into the needs, feelings and capabilities of people living with and without modern energy and related innovations and it contributes how these are mobilized and constrained in ways that may extend existing inequalities and the barriers to meaningful access, but also may signify means to overcome them.